(untitled) (Bangladesh Agronomy Journal, 2023)
The field experiment was carried out on chilli legume vegetables intercropping system using five treatments at the Agronomy Research Field of Bangladesh Agricultural Research Institute, Gazipur during rabi season, 2019-2020 and 2020-2021. The study was conducted to find out the suitable intercrop combination for higher productivity and economic return. The treatments were viz., T1= Sole chilli (60 cm × 50 cm), T2 = Chilli (100%) + one row bush bean (50%), T3= Chilli (100%) + two row bush bean (100%), T4= Chilli (100%) + one row pea (50%), T5= Chilli (100%) + two row pea (100%). Significantly the highest yield (8.67 t/ha) was obtained in sole chilli. But chilli + one inter row pea intercropping system gave the highest chilli equivalent yield (21.47 t/ha). The highest gross margin (Tk. 151896/ha) and BCR (3.42) were obtained from the same treatment. The results revealed that one row pea (50%) intercropped with chilli (100%) might be suitable intercrop combination for higher productivity and economic return. Bangladesh Agron. J. 2022, 25(2): 51-56